WHAT DOES #FREEDOM LOOK LIKE? INSTAGRAM AND THE VISUAL IMAGINATION OF VALUES - Scharlach, Rebecca; Trillo, Tommaso; Mizoroki, Saki; Kim, Bumsoo; Hallinan, Blake; Frosh, Paul; Shifman, Limor (AoIR Selected Papers of Internet Research, 2020)
Instagram is the place for the visualization of everything, from travel and food to abstract concepts such as compassion or freedom. While visualizing the abstract is not new, the platform has introduced a bottom-up process where users co-produce image repertoires that shape the boundaries of the imaginable. In this paper, we address an unexplored question about this process: which visual repertoires are associated with value-related terms on Instagram? We studied twenty widely used value hashtags, sampling the top 100 posts for each of them (N=2000). A combined qualitative-quantitative content analysis revealed that 19 of the 20 hashtags possessed a distinct visual footprint. These watermarks shared an orientation towards the self and an emphasis on consumption. We conclude by discussing three implications of our findings: the power of images to narrow the imagination of values, the distinction between “internalized” and “externalized” value depictions, and the meta-value of “aestheticized consumption” on Instagram.